REGIONAL CHARACTERISTICS OF THE DISTRIBUTION OF AUSTRALIAN MAINLAND SURFACE WATER (EXAMPLE OF RIVERS) (Scientific journal of the Fergana State University, 2024)
This article covers the geographical location of rivers and these rivers in the Australian mainland, and the size of the rivers and the volume of their flows geographically. A number of textbooks, atlases and internet pages were used in the preparation of the article. This article can be used in geography, hydrology classes of Higher Education and for those interested in the inland waters of the mainland.